Efficacy of dexmedetomidine in attenuating hemodynamic and airway responses during extubation: a randomized double-blind study - Pradhan, Kripa; Vaidya, Pradip Raj (Journal of Society of Anesthesiologists of Nepal, 2020)
Background Tracheal extubation causes significant hemodynamic changes and airway irritation. During smooth extubation there is absence of straining, movement, coughing, breath holding, laryngospasm and minimal change in hemodynamic. Purpose of this study was to evaluate the efficacy of dexmedetomidine in attenuating hemodynamic and airway responses during extubation. Methodology Eighty patients receiving general anesthesia were included in this randomized double-blind study. Ten minutes before the end of anesthesia, Group D (Dexmedetomidine group) (n=40) received Inj. Dexmedetomidine 0.5mcg/kg and Group N (Normal Saline group) (n=40) received 10 ml normal saline over 10 mins. Heart rate and mean arterial pressure were recorded prior to the drug administration till 10 mins after extubation. The incidence of cough was monitored during extubation. Any possible side effects of study drugs were recorded. Results Age, gender, physical status, weight, duration of surgery, baseline heart rate and mean arterial pressure were comparable between the groups. There was statistically significant difference (p < 0.05) in heart rate and mean arterial pressure between the groups after 5 mins of study drug administration and then throughout the study period. Using four point scale for coughing during extubation, 10% of Group D and 50% of Group N had minimal cough, 22.5% of Group N and 2.5% of Group D had moderate cough. Conclusion Finding suggests that intravenous dexmedetomidine before extubation significantly attenuates hemodynamic and airway responses during extubation.